Anemia prevention behavior in female adolescents and related factors based on Theory of Planned Behavior: A cross-sectional study - Halfie Zaqiyah Gusti Puspitasari; Ni Ketut Alit Armini; Retnayu Pradanie; Mira Triharini (Jurnal Ners, 2022)
Introduction: Female adolescent is a group prone to iron deficiency anemia due to various factors such as having monthly menstruation and poor diet. Therefore, anemia prevention behavior needs to be done from an early age to avoid prolonged health problems. The purpose of this study was to analyze the factors that correlated with anemia prevention behavior in female adolescents based on the Theory of Planned Behavior. Methods: This study used a descriptive correlational design with a cross-sectional approach. The population of this study is female adolescents in Madiun City. Purposive sampling was used to obtain 105 respondents. The instrument used was a questionnaire to measure the variables attitude, subjective norm, perceived behavioral control, intention, and anemia prevention behavior. Data analysis was performed using the Spearman Rho Test with a level of significance ≤ 0.05. Results: There is a relationship between attitudes (p = 0.003; r = 0.292), subjective norms (p = 0.006; r = 0.266), and perceived behavioral control (p= 0.002; r = 0.299) with the intention to prevent anemia and also perceived behavioral control (p = 0.003; r = 0.292) and intention (p = 0.000; r =0.392) with anemia prevention behavior. Conclusions: Better attitude, subjective norm, perceived behavioral control, and intention possessed by a female adolescent will make better anemia prevention behavior too. Therefore, support from various parties is needed to intensify the promotion of anemia prevention, education on early detection of anemia, especially for female adolescents, and further research to determine effective health promotion methods.